# SOLUTION: How do I solve this problem. It says to Simplify each expression. Where appropriate express answers with positive exponents. assume base is not zero. {{{4^-2*4^3}}}

Algebra ->  Algebra  -> Exponents-negative-and-fractional -> SOLUTION: How do I solve this problem. It says to Simplify each expression. Where appropriate express answers with positive exponents. assume base is not zero. {{{4^-2*4^3}}}      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Algebra: Negative and Fractional exponents Solvers Lessons Answers archive Quiz In Depth

 Question 94283: How do I solve this problem. It says to Simplify each expression. Where appropriate express answers with positive exponents. assume base is not zero. Answer by jayanthihemkos@yahoo.com(87)   (Show Source): You can put this solution on YOUR website!Since the base is same , we apply the law a^m*a^n = a^(m+n) Here m = -2 and n = +3 4^-2 *4^3 ==> 4^(-2+3) ==> 4^1 ==> 4 Hence the solution